2019
DOI: 10.3168/jds.2019-16524
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 2 different treatment procedures after calving to improve harvesting of high-quantity and high-quality colostrum

Abstract: The objective of this study was to evaluate 2 different treatment procedures at the first milking after calving to increase colostrum quantity and to improve colostrum quality in dairy cows. We hypothesized that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 44 publications
4
8
0
1
Order By: Relevance
“…The influence of the interval between calving and milking was described as statistically significant ( p = 0.013) and the calculated correlation coefficient was −0.22 [ 5 ]. In agreement with the results of Sutter et al (2019) [ 30 ], both studies described a negative correlation between the interval from calving to colostrum collection. Within a study by Scholz et al (2011) [ 70 ], there was a 41% decrease in the Ig concentration in the first 9 h after birth.…”
Section: Factors Associated With Ig Concentration In Colostrumsupporting
confidence: 92%
See 2 more Smart Citations
“…The influence of the interval between calving and milking was described as statistically significant ( p = 0.013) and the calculated correlation coefficient was −0.22 [ 5 ]. In agreement with the results of Sutter et al (2019) [ 30 ], both studies described a negative correlation between the interval from calving to colostrum collection. Within a study by Scholz et al (2011) [ 70 ], there was a 41% decrease in the Ig concentration in the first 9 h after birth.…”
Section: Factors Associated With Ig Concentration In Colostrumsupporting
confidence: 92%
“…The Enzyme-linked immunosorbent assay (ELISA) is frequently used to quantify Ig in colostrum [ 30 , 31 , 32 ]. An ELISA is based on the antigen-antibody reaction and is a method for detecting and quantifying Ig.…”
Section: Methods For Measuring the Immunoglobulin Concentration Of Colostrummentioning
confidence: 99%
See 1 more Smart Citation
“…The IgG concentration was assayed by a sandwich ELISA in the laboratory at Ludwig-Maximilian-University in Munich [21]. Laboratory methods were used according to Sutter et al [22].…”
Section: Methodsmentioning
confidence: 99%
“…IgG represents more than 85% of the total immunoglobulin (Turini et al, 2020). The concentration of IgG in colostrum is variable according to breed, lactation number, prepartum diet, calving season, dry period length, vaccination of the cow, and time of sample collection (Silva-Del-Río et al, 2017;Sutter et al, 2019). It has been reported that 30-50% of the colostrum contains insufficient amounts of IgG (Morrill et al, 2012;Bartier et al, 2015).…”
Section: Introductionmentioning
confidence: 99%